Simulation of production capacity using basic language / Faizul Azlan Abdullah. - Abdullah, Faizul Azlan (1991)
This project of production volume was originated by Encik Abdul Rahman Omar in his ' project The Management Game and presented in 1983. However in this report only part of the initial report taken to be improved, that is the production capacity section. In the previous management game, the production only takes into account the existing workers without acknowledge certain aspects about workers behavior in the organization. As understood, workers behavior is the most important aspect in a production organization. This has been rectified and modified to ensure that it is introduced into the game. However this program is made independently from the main program in the previous project. Certain modifications' have to be made to this program in order to suit the program into the main program. It is to be noted that only the production capacity with certain variables are taken into consideration. Other variables such as financial requirement are assumed enough to make the production run smoothly and is not considered in the program. The variables are-as the same as the previous report, which are workers (unskilled, semi-skilled and skilled), raw material, and machine available. Addition have been made in the workers variables such as incentive wages, effect of too many unskilled workers employed etc. It is program in such a way that the decision about these factors will affect the production volume.